Effects of light availability on crown structure, biomass production, light absorption and light-use efficiency of Hopea odorata planted within gaps in Acacia hybrid plantations. (1st November 2016) - Dong, Tran Lam; Forrester, David I.; Beadle, Chris; Doyle, Richard; Hoang, Nguyen Huy; Giap, Nguyen Xuan; Worledge, Dale
Abstract : Background : Young saplings of Hopea odorata, a native dipterocarp in Vietnam, require shading to prevent photoinhibition but they must avoid competition that stagnates their growth. Aims : To develop a silvicultural regime by examining how the biomass production of H. odorata changes along a light gradient in gaps within Acacia hybrid plantations. Methods : Hopea odorata saplings were planted in 22-m-diameter circular gaps within a 3-year-old Acacia hybrid plantation and in 5-m and 7.5-m-wide strip gaps within a 2.5-year-old Acacia hybrid plantation. Results : In the circular gap, biomass growth increased nearly tenfold from the gap perimeter (GP) to about 9 m from the perimeter, and then decreased. This was associated with a fivefold increase in the absorption of photosynthetically active radiation (APAR) and a nearly twofold increase in light-use efficiency (LUE). The increasing APAR was primarily related to increasing H. odorata crown sizes and a reduction in shading from the Acacia hybrid. In the strip gaps, the APAR was similar to that at the GP in the circular gap, however LUE was about threefold higher. Conclusions : Hopea odorata expressed plasticity in crown structure in response to incident light. While it grows under a wide range of availability of photosynthetically active radiation, growth increases strongly to a certain level of PAR. The best conditions for H. odorata growth were near the centre of the circular gaps, where PAR was 60% of full sunlight, while the strip gaps, where PAR was 20%, were too narrow owing to shading from the Acacia hybrid.